DEPICTION OF WOMEN AS A BODY IN SONIA FALEIRO’S BEAUTIFUL THING: INSIDE THE SECRET WORLD OF BOMBAY DANCE BARS - Rincy Philip , Dr. V.S. Bindhu (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Sonia Faleiro is a narrative figure of many non- fiction works. She travel all over India and explores the complication and sufferings of women and children. She is also the author of Beautiful Thing: Inside the Secret World of Bombay Dance Bars and a novel named The Girl. Faleiro is also a co- founder of Deca, a global co-operative of award winning journalists. Her writings acclaimed worldwide and appeared in The Newyork Times, The Financial Time and The California Sunday. Faleiro try to reveal a deplorable condition of women who sexually molested and repressed in Mumbai metropolis. Writer tries her best to illustrate masterfully the complexity of these living occurrences through her work Beautiful Thing: Inside the Secret World of Bombay Dance Bars. Many of these worked in these areas are addicted to drugs and they are suffering from severe and chronic sexually transmitted diseases with awful health conditions. For India, it is a shame that this much of secular country treat women as a body. This non- fiction work is a vivid portrayal of Faleiro’s journey to the world of dark and destructed souls.